Study of the tribological properties and ageing of alkyphosphonic acid films on galvanized steel - Peter Holliman (Tribology International, 2017)
The tribological properties of octyl-, dodecyl- or octadecylphosphonic acid coatings on TiO2-coated galvanized steel substrates have been studied using linear friction testing (LFT) as potential lubricants for deep drawing automotive steels. LFT data show that the coatings reduce the coefficient of friction by > 65% from 0.31 to <0.11. Confocal microscopy reveals that phosphonate-coated surfaces suffer considerably less wear than uncoated substrates during LFT. Water contact angle (WCA), XPS and IR data show that physisorbed phosphonates are removed by acetone washing leaving chemisorbed material. Data from a month-long ageing study using WCA, XPS and IR data shows that most of the physisorbed phosphonates become chemisorbed with time increasing hydrophobicity and tribological properties of the surfaces. Most of the changes occur within 14 days of coating and, after 21 days, no further surface changes were observed.